Gender Inequality in the Labor Market: Continuing Progress? - Francine D. Blau (Institute of Labor Economics (IZA), 2024)
This article examines the trends in women's economic outcomes in the United States focusing primarily on labor force participation, occupational attainment, and the gender wage gap. The author first highlights considerable progress on all dimensions prior to the 1990s followed by a slowing or stalling of gains thereafter, with a plateauing of female labor force participation trends and a slowing of women's occupational and wage convergence with men. She considers the likelihood of a resumption of progress in narrowing gender gaps in these areas, concluding it is unlikely without policy intervention. She then considers some new policy initiatives addressing work-family issues and labor market discrimination that may hold potential for increasing female labor force participation and narrowing gender inequities in the labor market.
Keywords: J16; J18; J21; J24; J31; J48; J71; 330; gender wage gap; gender; female labor force participation; occupational segregation; labor market discrimination; labor market policy